Tandem mass tag-based quantitative proteomics analysis reveals the new regulatory mechanism of progranulin in influenza virus infection - Li, Haoning; Zhang, Yuying; Li, Chengye; Ning, Peng; Sun, Hailiang; Wei, Fanhua (Frontiers in Microbiology, 2023)
Progranulin (PGRN) plays an important role in influenza virus infection. To gain insight into the potential molecular mechanisms by which PGRN regulates influenza viral replication, proteomic analyses of whole mouse lung tissue from wild-type (WT) versus (vs) PGRN knockout (KO) mice were performed to identify proteins regulated by the absence vs presence of PGRN. Our results revealed that PGRN regulated the differential expression of ALOX15, CD14, CD5L, and FCER1g, etc., and also affected the lysosomal activity in influenza virus infection. Collectively these findings provide a panoramic view of proteomic changes resulting from loss of PGRN and thereby shedding light on the functions of PGRN in influenza virus infection.